Social-environmental processes of technology and innovation. From the alchemist witches of yesterday to the environmental scientists of today: De las brujas alquimistas de ayer a las científicas ambientales de hoy (2019)
The social-environmental processes of technology and innovation that are in this work, are an alternative scientific approach, the result of a critical look at the way of thinking and doing science, from a dominant, masculine and elite science, built through centuries, excluding women and their ways of being, knowing, and understanding the world, the environment, and the world of sciences, in the plural. It shows, as well as the breaking of these paradigms, a group of researchers that reconstructs the line of women in scientific production and does it with their fellow men, in a new way of doing science, more egalitarian, plural and diverse, explained through the formative process of its area of research, as well as the results of their scientific production